COFFEE GROUND COMPOSITION AND ANODE MATERIAL FOR SECONDARY BATTERY COMPRISING THE SAME

By inserting the nanosilicon compound into the gap of the coffee grounds and heat treatment and carbonization, the instability problem caused by volume expansion of the silicon cathode material during charging and discharging is solved, and the effect of improving battery capacity and life, reducing manufacturing costs and environmental pollution is achieved.

JP7663258B2Active Publication Date: 2025-04-16マグナテク シオー エルティーディー
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023118573
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-01-17
Filing Date
2023-07-20
Publication Date
2025-04-16
Estimated Expiration
2043-07-20

AI Technical Summary

Technical Problem

The instability caused by volume expansion and contraction of silicon cathode active materials during charging and discharging leads to silicon breakage and peeling, reducing the life and capacity of the battery.

Method used

Coffee grounds are used as part of the negative electrode material, and nanosilicon compounds are inserted into the gaps of the coffee grounds, and a negative electrode material with high conductivity and increased capacity is formed through heat treatment and carbonization processes.

Benefits of technology

It effectively suppresses the breakage and peeling phenomenon caused by silicon volume expansion, improves charge and discharge characteristics, such as primary efficiency, capacity and life characteristics, and reduces manufacturing costs while reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663258000015
    Figure 0007663258000015
  • Figure 0007663258000016
    Figure 0007663258000016
  • Figure 0007663258000017
    Figure 0007663258000017
Patent Text Reader

Abstract

To provide: coffee grounds composition which can suppress the phenomenon of silicon crushing and peeling caused by volume expansion during charging and discharging and improves charging and discharging characteristics such as initial efficiency, capacity, and lifespan characteristics; and a negative electrode material for a secondary battery comprising the same.SOLUTION: A coffee grounds composition may have a tap density of 0.48 g / cm3 and a particle diameter D50 of 317.14 μm. The coffee grounds composition may show two peaks at 2θ between 30 and 40 degrees, may show one peak at 2θ between 40 and 45 degrees, and may show one peak at 2θ between 45 and 50 degrees in XRD analysis.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coffee grounds composition and a negative electrode material for a secondary battery containing the same. [Background technology]

[0002] Recently, as the demand for ultra-large-scale power storage systems, as well as various small and lightweight electronic devices, has rapidly increased, there has been a growing interest in new energy sources worldwide. Among these, research and development has focused on the field of lithium secondary batteries, which are environmentally friendly, have high energy density, and can be rapidly charged and discharged.

[0003] In particular, carbon-based, metal-based, and oxide-based materials used as negative electrode active materials in lithium secondary batteries are not only available in a wide variety of types, but are also being extensively researched and commercialized because they play a key role in improving high-output, high-density energy power.

[0004] Among these, silicon has been attracting attention as one of the new negative electrode active materials due to its electrochemical reduction potential of 0.4 V and high capacity of 4,200 mAh / g.

[0005] Although silicon has a very high capacity, unlike carbon-based or metal-based negative electrode active materials, silicon undergoes volume expansion and contraction of 300% or more during charging and discharging.

[0006] Such a large volume change of silicon forms an unstable solid electrolyte interphase (SEI), which causes detachment from the current collector, resulting in poor life characteristics and capacity loss.

[0007] In addition, due to the low electrical conductivity of silicon, the lithium ion diffusion rate in silicon material is also slow, which adversely affects the rate capability of silicon.

[0008] Therefore, research is ongoing to find a method for alleviating such a sudden volume change to obtain long life characteristics and high capacity characteristics, and to fabricate a structure with a high surface area to improve the rate-limiting characteristics by shortening the ion transmission distance.

[0009] Nano-sized carbon-based materials, which are often used as composites with silicon, have high electrical conductivity, large surface area, and thermal and chemical stability, and can improve the rate-limiting properties of silicon.

[0010] Furthermore, by providing a structure that reduces the volume change of silicon, the effect of increasing capacity and improving life characteristics can be obtained, and this is a trend that is receiving a lot of research.

[0011] In this regard, a technique has been disclosed in Registered Patent Publication No. 10-0903503 (announcement date: May 8, 2009) (hereinafter referred to as Prior Art 1).

[0012] Such prior art 1 is a technology for providing an anode active material having significantly improved life characteristics by including carbon nanotubes (CNTs) having a length of 0.1 to less than 10 μm and silicon particles disposed in the internal space of the carbon nanotubes, a manufacturing method thereof, and a lithium secondary battery including the anode active material.

[0013] Furthermore, a prior art has been disclosed in Registered Patent Publication No. 10-1613518 (March 4, 2016) (hereinafter referred to as Prior Art 2).

[0014] Prior Art 2 relates to a method for producing a carbon-silicon composite electrode material comprising silicon nanoparticles and a porous carbon structure having an inverse opal structure, a carbon-silicon composite electrode material produced by the method, and a secondary battery comprising the carbon-silicon composite electrode material.

[0015] As a result, the conventional technique 2 can produce a carbon-silicon composite electrode material including silicon nanoparticles and a porous carbon structure with an inverse opal structure in a simple manner by dry and wet mixing. In addition, a secondary battery produced using the carbon-silicon composite electrode material including silicon nanoparticles and a porous carbon structure with an inverse opal structure has excellent charge / discharge capacity and life characteristics, and the technique allows for composition control of the carbon-silicon composite electrode material including silicon nanoparticles and a porous carbon structure with an inverse opal structure.

[0016] Furthermore, a prior art has been disclosed in Published Patent Application No. 10-2015-0113314 (announcement date: 2015.10.08.) (hereinafter referred to as Prior Art 3).

[0017] Such prior art 3 relates to an anode material, a non-aqueous lithium secondary battery having the same, and a manufacturing method thereof, and provides an anode material having a simple manufacturing process, high initial efficiency, and excellent electrochemical properties. Prior art 3 also provides a method for obtaining an anode material by dry-mixing a spherical carbon-based material, silicon nanoparticles, and an amorphous carbon raw material to form a mixture, adding the mixture to a solvent, stirring, and drying the mixture, and then adsorbing the silicon nanoparticles and the amorphous carbon raw material on the surface of the carbon-based material. The carbon-based material to which the silicon nanoparticles and the amorphous carbon raw material are adsorbed is then heat-treated to form a coating layer containing silicon nanoparticles and amorphous carbon on the surface of the carbon-based material, thereby obtaining the anode material.

[0018] On the other hand, Published Patent Application No. 10-2022-0052251 (Announcement date: April 27, 2022) (hereinafter referred to as Prior Art 4) has been disclosed.

[0019] Prior Art 4 relates to a method for producing a metal-carbon composite using coffee grounds as a carbon source and a reducing agent, and more specifically, it is a technology that provides a method for producing a metal-carbon composite including the steps of mixing a metal oxide and dried coffee grounds to produce a metal oxide-coffee grounds composite, and heat-treating the produced metal oxide-coffee grounds composite to carbonize and reduce it.

[0020] As a result, the metal-carbon composite manufacturing method of Conventional Technology 4 is environmentally friendly because it reuses discarded coffee grounds, and it is an economically advantageous technology because it can shorten the manufacturing time by simultaneously carrying out the carbonization process of the coffee grounds and the reduction process of the metal oxide in a single process.

[0021] Furthermore, a prior art has been disclosed in Registered Patent Publication No. 10-1334594 (announcement date: 2012.06.18.) (hereinafter referred to as Prior Art 5).

[0022] Prior Art 5 is a technology for providing an anode material for secondary batteries that absorbs and releases ions, which comprises a core containing a crystalline carbon-based material, and a composite coating layer containing one or more materials selected from the group consisting of low-crystalline carbon and amorphous carbon, and a hydrophilic material, the composite coating layer having a structure in which a matrix made of one or more materials selected from the group consisting of low-crystalline carbon and amorphous carbon, and one component selected from a hydrophilic material, contains a filler made of the remaining components, and a secondary battery including such an anode material.

[0023] Silicon is a high-performance material that has a theoretical capacity (4,200 mAh / g) ten times higher than that of graphite, but it is also a material that has many problems during charging and discharging.

[0024] The problems that silicon negative electrode active materials encounter when they are charged and discharged can be broadly divided into three categories. First, the silicon negative electrode active material changes in volume by approximately 400%, causing cracks in the silicon outer particles and reducing performance. In addition, the conductive path between the silicon and graphite is broken, causing peeling. Furthermore, when silicon and graphite are synthesized and used, charging during synthesis causes volume expansion to the extent that it destroys the SEI layer, consuming lithium and generating gas.

[0025] This volume expansion can be improved by inserting silicon into the voids in the coffee grounds and carbonizing them. Carbonization has the effect of improving electrical conductivity and capacity, and there is a demand for development in this area. [Prior art documents] [Patent documents]

[0026] [Patent Document 1] Registered Patent Publication No. 10-0903503 (Publication Date: 2009.05.08) [Patent Document 2] Registered Patent Publication No. 10-1613518 (March 4, 2016) [Patent Document 3] Published Patent Publication No. 10-2015-0113314 (Publication date: 2015.10.08.) [Patent Document 4] Published Patent Publication No. 10-2022-0052251 (Publication date: 2022.04.27.) [Patent Document 5] Registered Patent Publication No. 10-1334594 (Publication date: 2012.06.18.)

[0027] Contents of the invention Problem to be solved The present invention has been made to solve the above problems, and an object of the present invention is to provide a coffee grounds composition that can suppress silicon fracture and peeling caused by volume expansion during charging and discharging, and has improved charge and discharge characteristics such as initial efficiency, capacity, and life characteristics, and a negative electrode material for secondary batteries containing the same.

[0028] However, the technical problems to be solved by the present invention are not limited to those mentioned above, and other technical problems not mentioned will be clearly understood by a person having ordinary skill in the art to which the present invention pertains from the following description.

[0029] Means for solving the problem The coffee grounds composition according to one embodiment of the present invention has a tap density of 0.48 g / cm 3 and the particle size D50 is 317.14 μm.

[0030] In a negative electrode material for a secondary battery containing a coffee grounds composition according to another embodiment of the present invention, the negative electrode material exhibits two peaks between 2θ of 30 and 40 degrees, three peaks between 2θ of 40 and 45 degrees, and two peaks between 2θ of 45 and 50 degrees in an XRD analysis.

[0031] Effect of the Invention The present invention can contribute to protecting the natural environment by producing a high-capacity silicon negative electrode active material for lithium secondary batteries using coffee grounds, which is an environmental pollutant, and the high-capacity silicon negative electrode active material using coffee grounds can reduce the manufacturing costs of negative electrode materials for lithium secondary batteries.

[0032] In addition, the present invention can suppress silicon fracture and peeling caused by volume expansion during charging and discharging.

[0033] Furthermore, the present invention can improve the charge / discharge characteristics, such as initial efficiency, capacity, and life characteristics. [Brief description of the drawings]

[0034] [Figure 1] 1 is a graph showing the results of XRD measurement of a coffee grounds composition according to one embodiment of the present invention. [Diagram 2] 1 is a graph showing the results of XRD measurement of a negative electrode material for a secondary battery including a coffee grounds composition according to an embodiment of the present invention. [Diagram 3] 1 is a graph showing the results of Raman spectroscopy of a coffee grounds composition according to one embodiment of the present invention. [Figure 4] 1 is a graph showing the results of Raman spectroscopy of a negative electrode material for a secondary battery including a coffee grounds composition according to an embodiment of the present invention. [Diagram 5] 1 is a graph showing the results of X-ray photoelectron spectroscopy (XPS) measurement of a coffee grounds composition according to an embodiment of the present invention. [Figure 6] 1 is a graph showing the results of X-ray photoelectron spectroscopy measurement of a negative electrode material for a secondary battery including a coffee grounds composition according to an embodiment of the present invention. [Figure 7] FIG. 2 is a diagram showing the tap density and particle size analysis results of a coffee grounds composition according to an embodiment of the present invention. [Figure 8] FIG. 8 is a diagram showing the tap density and particle size analysis results of a negative electrode material for a secondary battery including a coffee grounds composition according to an embodiment of the present invention. [Figure 9] SEM image showing coffee grounds collected at a specialty coffee shop. [Figure 10] 1 is a SEM image showing the insertion of nanosilicon into the macro- and micro-voids of coffee grounds. [Figure 11a] These are SEM images of silicon anode active material with nanosilicon mixture inserted into the voids of coffee grounds before and after heat treatment. [Figure 11b] These are SEM images of silicon anode active material with nanosilicon mixture inserted into the voids of coffee grounds before and after heat treatment. [Figure 12] 1 is a graph showing charge / discharge characteristics of a silicon active material test battery. [Figure 13] 1 is a graph showing charge / discharge characteristics of a silicon active material test battery. [Figure 14] 1 is a diagram related to experimental data for tap density for Examples 0, 1, and 1-1 to 1-8, where Sample No. 1 is for Example 0 and Sample No. 6 is for Example 1. [Figure 15] FIG. 1 is a diagram of experimental data for tap density for Examples 0, 1, and 1-1 to 1-8. [Figure 16] FIG. 2 is a sequence diagram of a method for manufacturing a silicon anode active material according to an embodiment of the present invention. [Figure 17] FIG. 2 is a sequence diagram of a method for manufacturing a silicon anode active material according to an embodiment of the present invention.

[0035] Specific details for carrying out the invention Hereinafter, the embodiments of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art to which the present invention pertains can easily carry out the embodiments. However, since the description of the present invention is merely an embodiment for structural or functional description, the scope of the present invention should not be interpreted as being limited by the embodiments described herein. In other words, since the embodiments can be modified in various ways and can have various forms, the scope of the present invention should be understood to include equivalents that can realize the technical idea. In addition, the objectives or effects presented in the present invention do not mean that a specific embodiment should include all of them or should include only such effects, and therefore the scope of the present invention should not be understood to be limited thereby.

[0036] The meanings of the terms in the present invention are understood as follows.

[0037] Terms such as "first" and "second" are used to distinguish a certain component from other components, and should not be used to limit the scope of rights. For example, a first component can be named a second component, and similarly, a second component can be named a first component. When a component is "connected" to another component, it should be understood that the component can be directly connected to the other component, but there may be other components in between. In contrast, when a component is "directly connected" to another component, it should be understood that there is no other component in between. Meanwhile, other expressions describing the relationship between components, such as "between" and "immediately between", or "adjacent to" and "directly adjacent to", should be analyzed in the same way.

[0038] The singular includes the plural unless the context clearly dictates differently. Furthermore, terms such as "comprise" or "have" are intended to specify the presence of stated features, numbers, steps, operations, components, parts, or combinations thereof, and should be understood not to exclude the possible presence or addition of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0039] All terms used herein, unless otherwise defined, have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention pertains. Terms defined in commonly used dictionaries should be interpreted as being consistent with the meaning they have in the context of the relevant art, and cannot be interpreted as having an ideal or overly formal meaning unless expressly defined in the present invention.

[0040] Description of Coffee Grounds Composition The coffee grounds of the present invention are a by-product remaining after coffee beans are roasted and ground, then hydrated and heat-treated to extract coffee liquid, and 99.8% of them are discarded. Coffee grounds contain components such as protein, fiber, sugars, polyphenol compounds, cellulose, hemicellulose, and lignin, as well as tocopherol, polyphenols, and non-polyphenol compounds that were not extracted during the coffee hot water extraction process, and Maillard reaction polymers generated during the roasting process, and carbon, nitrogen, and silicon remain during carbonization.

[0041] Unless this coffee grounds is recycled, a large amount of it will be treated as industrial waste, causing environmental pollution. In Korea, coffee grounds are supplied as a source of boiler fuel for coffee production factories, and some are used as animal feed, fertilizer additives, functional substance sources, biodiesel raw materials, culture soil mixtures for mushroom cultivation, and activated carbon. Large quantities of coffee grounds are produced in the coffee industry during the process of making coffee foods, and only a very small portion is recycled in the composting process.

[0042] The coffee grounds in the present invention are most preferably coffee grounds (coffee by-products, coffee residue) collected at specialty coffee stores, and the amount of coffee grounds mixed is preferably 3 to 19% by weight based on the total weight.

[0043] Negative electrode active material and method for producing same As shown in FIG. 16, the method for manufacturing a silicon negative active material having a nanosilicon mixture inserted into the voids of coffee grounds according to the present invention includes a nanosilicon preparation step (S11) of preparing nanosilicon, a surfactant preparation step (S12) of preparing an anionic surfactant, a silane preparation step (S13) of preparing a silane, a mixed dispersion preparation step (S14) of preparing a mixed dispersion based on ultrapure distilled water, a coffee grounds preparation step (S15) of drying coffee grounds, a polyvinyl alcohol mixing step (S16) of mixing polyvinyl alcohol into the mixed dispersion, and a polyvinyl alcohol mixing step (S17). The method includes a step of mixing polyamic acid into the mixed dispersion (S21), a step of mixing polyamic acid into the mixed dispersion (S22), a step of mixing graphite into the mixed dispersion (S23), a step of mixing vegetable oil into the mixed dispersion (S24), a step of heat treating the final mixed dispersion (S31), a step of obtaining a silicon active material of a certain size using an ultrasonic vibration screen (S32), a step of obtaining a final product by inserting nanosilicon into the voids of the coffee grounds (S33), and a step of obtaining a negative electrode active material by inserting the nanosilicon mixture (SiO2, SiC) into the voids of the coffee grounds (S34).

[0044] As an example of a means for carrying out the silicon negative electrode active material manufacturing method, nanosilicon is composed of one or more types of silicon selected from the group consisting of silicon (Si), silicon dioxide (SiO2), and silicon carbide (SiC). Considering compatibility with other components, the size is most preferably 20 to 100 nm, and the mixed amount is preferably 0.5 to 4 wt % of silicon dioxide (SiO2) and 0.2 to 1.3 wt % of silicon carbide (SiC) based on the total weight.

[0045] The surfactant is composed of one or more selected from the group consisting of anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, and special surfactants. Considering the synergistic effect with other components, an anionic surfactant is preferable. The mixed amount is preferably 1 to 9 wt % of the anionic surfactant primary and 7 to 8 wt % of the secondary surfactant based on the total weight.

[0046] The silane is at least one selected from the group consisting of chlorosilane, alkoxysilane, and silazane, and alkoxysilane (methyltrimethoxysilane: (CH3O)3SiCH3) is the most preferable. The amount of alkoxysilane mixed is preferably 6 to 7% by weight based on the total weight.

[0047] Furthermore, the distilled water is at least one selected from the group consisting of primary distilled water, secondary distilled water, and tertiary distilled water. The tertiary distilled water is most preferably ultrapure distilled water (tertiary distilled water) having an underwater conductivity value of 0.055 μS or less and from which contaminants (particles, ions, microorganisms, organic matter, etc.) have been 100% removed. The amount of the mixture is preferably 35 to 60% by weight based on the total weight.

[0048] The water-soluble polymer is at least one selected from the group consisting of polyvinyl alcohol, starch, rubber, starch derivatives, cellulose derivatives, and non-ionic water-soluble polymers. Considering the synergistic effect with other components, polyvinyl alcohol is preferable, and the mixed amount is preferably 0.1 to 0.5 wt % based on the total weight.

[0049] Furthermore, the polyamic acid is preferably a hydrophilic polymer that can be used as an emulsion stabilizer, a thickener, a film former, or an adhesive, and the amount of the polyamic acid mixed is preferably 1 to 1.5% by weight based on the total weight.

[0050] Furthermore, the negative electrode active material to be mixed is composed of one or more selected from the group consisting of natural graphite, artificial graphite, low crystalline carbon (soft / hard carbon), and metal (silicon). Considering the synergistic effect with other components, natural graphite is preferable, and the mixed amount is preferably 10 to 15 wt % based on the total weight.

[0051] Finally, the oil is at least one selected from the group consisting of vegetable oil, animal oil, fuel oil, solid oil, industrial oil, and lubricating oil, and is preferably an inexpensive vegetable oil, and the mixed amount is preferably 7 to 8 wt % based on the total weight.

[0052] In addition, in order to achieve the object of the present invention, the evenly dispersed final mixed dispersion must be heat-treated before layers are formed according to specific gravity, and the final mixed dispersion is heat-treated at 800 to 900°C in air and carbonized to obtain a silicon anode active material final product.

[0053] That is, in the method for manufacturing the silicon negative active material of the present invention, as shown in FIG. 17, two or more kinds of nanosilicon (A1) having a size of 20 to 100 nm are prepared, and then an anionic surfactant (A2) and a silane (A3) are prepared. Then, ultrapure distilled water, which is a tertiary distilled water, is prepared as an aqueous solution for preparing a primary mixed dispersion. In the initial process of manufacturing the silicon negative active material, A1, A2, and A3 are primarily mixed with the ultrapure distilled water, and the primary mixed dispersion is mixed with coffee grounds (C1) by adding an anionic surfactant to the primary mixed dispersion, and then mixed and dispersed.

[0054] As shown in FIG. 17, B1 to B7 are dispersed using an ultrasonic disperser to produce a mixed dispersion, which is then mixed sequentially with coffee grounds (C1), polyvinyl alcohol (C2), polyamic acid (C3), natural graphite (C4), vegetable oil (C5), etc.

[0055] Here, in B7, the sixth mixed dispersion liquid is first evaporated at 300 to 380° C. to evaporate water, and then carbonized at 800 to 900° C. for 1 hour to obtain a silicon negative electrode active material final product.

[0056] In the method of manufacturing the silicon negative active material of the present invention shown in FIG. 16, more preferably, the nanosilicon preparation step (S11) includes the steps of preparing 20 nm silicon dioxide (CN VISION: CNSi-01) by mixing 1 to 0.68 wt% of 100 wt% of total ultrapure distilled water and drying at 100 to 130° C., preparing 50 nm silicon carbide (Avention: Silicon Carbide) by mixing 1 to 0.26 wt% of 100 wt% of total ultrapure distilled water and drying at 100 to 130° C., and drying the silicon (Silicon) to remove moisture contained therein.

[0057] In the surfactant preparation step (S12), an anionic surfactant, which dissociates in water and produces an anion that adsorbs on the surface of the aqueous solution to reduce surface tension, is used in an amount of 1 to 7.5 wt % of the total ultrapure distilled water (100 wt %), selected from sodium lauryl ether sulfate, sodium α-olefin sulfonate, and alkyl dimethylamine oxide.

[0058] In the silane preparation step (S13), alkoxysilane (methyltrimethoxysilane: (CH3O)3SiCH3) used to make an inorganic surface hydrophobic is used in an amount of 1 to 6.25 wt% mixed with 100 wt% of ultrapure distilled water.

[0059] In the mixed dispersion preparation step (S14), nanosilicon, anionic surfactant, silane, coffee grounds, polyvinyl alcohol, polyamic acid, natural graphite, and vegetable oil are mixed and dispersed in deionized water.

[0060] The coffee grounds preparation step (S15) is a step of preparing coffee grounds by drying them at 130° C., and the coffee grounds are mixed with ultrapure distilled water in an amount of 10 to 3.66 wt % of the total amount of 100 wt %. The coffee grounds used in this process are immersed in a hydroxide solution (potassium hydroxide: KOH, sodium hydroxide: NaOH, potassium hydroxide: Ca(OH)2) to obtain a plurality of voids, and after the hydroxide solution is removed from the coffee grounds, they are heat-treated and do not go through an activated carbonization process. Therefore, there is no water washing process in the entire process from collection to production of the final negative active material.

[0061] In the polyvinyl alcohol mixing step (S21), the polyvinyl alcohol is mixed in an amount of 1 to 0.5 wt % of the total ultrapure distilled water mixture (100 wt %).

[0062] In the polyamic acid mixing step (S22), the polyamic acid is mixed in an amount of 1 to 1.37 wt % of the total ultrapure distilled water mixture (100 wt %).

[0063] In the graphite mixing step (S23), the natural graphite (T-360: TOB) is mixed in an amount of 1 to 15 wt % of the total ultrapure water / distilled water mixture (100 wt %).

[0064] In the vegetable oil mixing step (S24), the vegetable oil is mixed in an amount of 1 to 7.5 wt % of the total ultrapure distilled water mixture (100 wt %).

[0065] The final mixed dispersion heat treatment step (S31) is a sixth mixed dispersion final heat treatment step, which includes a first drying step at 300 to 380°C and a second heat treatment step at 800 to 900°C.

[0066] In the silicon active material obtaining step (S32), the coffee grounds mixed with the nanosilicon and graphite described above are ground in an automatic grinding mill and sorted using an ultrasonic vibration screen (160#-96 μm) to obtain a coffee grounds nanosilicon negative electrode active material composite that can be used as a negative electrode material.

[0067] Anode and method for producing the same The negative electrode of the present invention contains the above-mentioned negative electrode active material of the present invention.

[0068] The negative electrode of the present invention is produced by dissolving or dispersing the above-mentioned negative electrode active material of the present invention and a conductive material and / or a binder in a solvent to produce a negative electrode mixture, applying the negative electrode mixture to at least one surface of a negative electrode current collector, and then drying and pressing the mixture. Alternatively, the negative electrode mixture is cast on another support, and then the film obtained by peeling the mixture from the support is laminated on the negative electrode current collector.

[0069] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and examples of the negative electrode current collector include copper, stainless steel, aluminum, nickel, titanium, plastic carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, and aluminum-cadmium alloy. The negative electrode current collector generally has a thickness of 3 μm to 500 μm, and the surface of the current collector may be provided with fine irregularities to strengthen the binding force of the negative electrode active material. The negative electrode current collector may be used in various forms, such as a film, sheet, foil, net, porous body, foam, and nonwoven fabric.

[0070] The negative electrode active material is included in an amount of 80 to 99 wt %, more specifically, 85 to 98 wt %, based on the total weight of the negative electrode active material layer, to provide excellent capacity characteristics.

[0071] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives. Of these, one type alone or a mixture of two or more types is used. The conductive material is contained in an amount of 1 wt % to 30 wt % based on the total weight of the negative electrode active material layer.

[0072] The binder also serves to improve adhesion between negative active material particles and between the negative active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-co-hexafluoropropylene (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder is included in an amount of 1 wt% to 30 wt% based on the total weight of the negative active material layer.

[0073] Meanwhile, the solvent used in the preparation of the negative electrode composite is a solvent generally used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, or the like, either alone or in combination. The amount of the solvent used is appropriately adjusted in consideration of the coating thickness, production yield, viscosity, etc. of the slurry.

[0074] Lithium secondary battery Next, the lithium secondary battery according to the present invention will be described.

[0075] The negative electrode of the present invention is usefully used in the manufacture of lithium secondary batteries.

[0076] Specifically, the lithium secondary battery according to the present invention includes a negative electrode, a positive electrode facing the negative electrode, a separator sandwiched between the negative electrode and the positive electrode, and an electrolyte, wherein the negative electrode is prepared by coating the negative electrode active material according to the present invention.

[0077] Meanwhile, the secondary battery further includes a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0078] The lithium secondary battery is manufactured by a conventional method for manufacturing a secondary battery, except that the negative electrode according to the present invention is used.

[0079] The present invention will be described in more detail below by dividing it into preferred examples and comparative examples.

[0080] <Example 0> The coffee by-products and coffee grounds were dried to provide a coffee grounds composition.

[0081] <Example 1> Silicon dioxide (CN VISION SiO2: CNSi-01) 20 nm 0.68 wt% and silicon carbide (Avention SiC: Silicon Carbide) 50 nm 0.26 wt% were prepared by drying at 130°C, followed by 7.5 wt% containing additional anionic surfactant and 6.25 wt% silane.

[0082] Next, deionized water is added in an amount of 57.28 wt%, followed by the addition of silicon dioxide, silicon carbide, surfactant, and silane, in that order, and then the mixture is mixed and dispersed for 30 minutes using an ultrasonic disperser (VCX-750) to prepare a primary mixed dispersion.

[0083] An additional amount of surfactant and 3.66 wt% coffee grounds collected at a coffee specialty store and dried at 130°C were added to the primary mixed dispersion, and the mixture was dispersed for 30 minutes using an ultrasonic disperser to prepare a secondary mixed dispersion.

[0084] The coffee grounds used in this process are not those that are soaked in a hydroxide solution (potassium hydroxide: KOH, sodium hydroxide: NaOH, potassium hydroxide: Ca(OH)2) to obtain multiple pores, and then heat-treated to be converted into activated carbon after the hydroxide solution is removed from the coffee grounds. Instead, the coffee grounds used are those collected from coffee specialty stores. The coffee grounds used in this process do not undergo a water washing process throughout the entire process, from collection to production of the final negative electrode active material.

[0085] 0.5 wt % of polyvinyl alcohol is added to the second mixed dispersion liquid, and then dispersed for 30 minutes using an ultrasonic disperser to prepare a third mixed dispersion liquid.

[0086] 1.37 wt % of polyamic acid is added to the tertiary mixed dispersion, and then dispersed for 30 minutes using an ultrasonic disperser to prepare a quaternary mixed dispersion.

[0087] 15 wt % of natural graphite (T-360: TOB) is added to the fourth mixed dispersion, and then dispersed for 30 minutes using an ultrasonic disperser to prepare a fifth mixed dispersion.

[0088] After adding 7.5 wt % of a vegetable organic compound (oil: vegetable oil) to the fifth mixed dispersion, it is dispersed for 30 minutes using an ultrasonic disperser to prepare the final sixth mixed dispersion.

[0089] The sixth mixed dispersion is heat-treated at 900°C to carbonize the coffee grounds, thereby obtaining a negative electrode active material in which nanosilicon is inserted into the coffee grounds, as shown in Figure 10.

[0090] The nanosilicon-intercalated coffee grounds obtained through this process can be used as a negative electrode active material without a water washing process.

[0091] Coffee grounds mixed with nanosilicon and graphite were ground in an automatic grinding mill and sorted to a size that could pass through an ultrasonic vibration screen (160#-96 μm) to produce negative electrode material for secondary batteries.

[0092] <Example 2> A negative active material was prepared in the same manner as in Example 1, except that the mixture contained 7.32 wt % coffee grounds, 1.36 wt % SiO2, 0.52 wt % SiC, and 52.68 wt % ultrapure distilled water.

[0093] <Example 3> A negative active material was prepared in the same manner as in Example 1, except that the mixture contained 10.98 wt % coffee grounds, 2.04 wt % SiO2, 0.78 wt % SiC, and 48.08 wt % ultrapure distilled water.

[0094] <Example 4> A negative active material was prepared in the same manner as in Example 1, except that the mixture contained 14.64 wt% coffee grounds, 2.72 wt% SiO2, 1.04 wt% SiC, and 43.48 wt% ultrapure distilled water.

[0095] <Example 5> A negative active material was prepared in the same manner as in Example 1, except that the mixture contained 18.3 wt % coffee grounds, 3.4 wt % SiO2, 1.3 wt % SiC, and 33.88 wt % ultrapure distilled water.

[0096] <Comparative Example 1> A negative active material was prepared in the same manner as in Example 1, except that the mixture contained 0 wt % coffee grounds, 3.4 wt % SiO2, 1.3 wt % SiC, and 57.18 wt % ultrapure distilled water.

[0097] <Comparative Example 2> A negative active material was prepared in the same manner as in Example 1, except that the mixture contained 18.3 wt % coffee grounds, 0 wt % SiO2, 1.3 wt % SiC, and 42.28 wt % ultrapure distilled water.

[0098] <Comparative Example 3> A negative active material was prepared in the same manner as in Example 1, except that the mixture contained 18.3 wt % coffee grounds, 3.4 wt % SiO2, 0 wt % SiC, and 40.18 wt % ultrapure distilled water.

[0099] The contents of each ingredient for Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Table 1 below.

[0100] [Table 1]

[0101] In addition, as described below, based on Example 1, which was determined to have the best performance, the proportions of coffee grounds, SiO2, and SiC were adjusted to ±5, 10, 20, and 30 wt%, respectively, and additional experiments were conducted on Examples 1-1 to 1-8 below.

[0102] The experimental method for Examples 1-1 to 1-8 was the same as that for Example 1, except that the contents of coffee grounds, SiO2, and SiC were different as shown in Table 2 below.

[0103] [Table 2]

[0104] <Manufacturing Example> Fabrication of a lithium secondary battery containing silicon anode active material by inserting nanosilicon mixture into the voids of coffee grounds The materials according to the examples and comparative examples were mixed to prepare a full cell (65 mm×50 mm 5T) as a negative electrode active material, and data was measured.

[0105] The negative electrode according to the present invention was prepared by preparing a negative electrode slurry using a mixture of silicon negative electrode material with nanosilicon inserted into the voids of coffee grounds: artificial graphite (MCMB: MesoCarbon MicroBeads): acetylene black: CMC (Carboxymethyl Cellulose): SBR (Styrene-Butadiene Rubber) = 15:79:2:2:2 wt%. The negative electrode slurry was coated on a negative electrode current collector with a thickness of 180 μm using a TOB coating machine (Slot Die Coating Machine), and then dried in a vacuum at 130°C for 6 hours.

[0106] For the positive electrode, a positive electrode slurry was prepared with a mixture ratio of NMC811 (LiNi0.8Mn0.1Co0.102): acetylene black: PVDF (Polyvinylidene fluoride) = 96:2:2 wt%, and the positive electrode slurry was coated on a positive electrode current collector with a thickness of 250 μm using a TOB coating machine, and then the electrode was dried in a vacuum at 130 °C for 6 hours.

[0107] The full cell assembly was assembled in an argon-filled glove box.

[0108] The electrolyte used was a mixture of 1M lithium hexafluorophosphate (LiPF6) and ethylene carbonate (EC): dimethyl carbonate (DMC): diethyl carbonate (DEC) in a volume ratio of 1:1:1. A wet separation membrane was used to fabricate a full cell.

[0109] <Experimental Example 1> Electrochemical property evaluation The full cell prepared in the above Preparation Example was charged to 4.2 V and discharged to 2.8 V, and the charge capacity (mAh / g), discharge capacity (mAh / g), and initial charge / discharge efficiency (%) were measured.

[0110] Further, the full cells prepared for each sample in the above manufacturing examples were subjected to 50 cycle characteristics determination.

[0111] The charge and discharge capacities and the initial charge and discharge efficiencies are shown in Table 3 below.

[0112] [Table 3]

[0113] 12 and 13 are graphs showing the results of 50 cycles of charge / discharge testing of a battery using a silicon negative electrode active material for a lithium secondary battery in which nanosilicon is inserted into coffee grounds. The results show that the mixture amount of Example 1 shows the best charge / discharge cycle characteristics.

[0114] Conventionally, when nanosilicon is used as a negative electrode active material, there is a problem that volume expansion occurs during charging and discharging, which reduces capacity. In order to prevent volume expansion, the present invention inserts nanosilicon into the voids in the coffee grounds, thereby maximally controlling the expansion of nanosilicon, and by using coffee grounds, which are environmental pollutants, to manufacture a negative electrode active material, it is possible to protect the environment and reduce manufacturing costs.

[0115] In particular, since there is no water washing process in the entire process of producing the negative electrode active material, water pollution problems during the manufacturing process can be prevented.

[0116] <Experimental Example 2> XRD analysis results FIG. 1 is a graph showing the results of an XRD measurement of a coffee grounds composition according to one embodiment of the present invention, and FIG. 2 is a graph showing the results of an XRD measurement of a negative electrode material for a secondary battery including a coffee grounds composition according to one embodiment of the present invention.

[0117] First, the coffee grounds composition of Example 0 was subjected to XRD measurement, and the graph of the results is shown in FIG.

[0118] Referring to FIG. 1 and Tables 4 and 5 below, it can be seen that the coffee grounds composition shows two peaks between 30 and 40 degrees 2θ, one peak between 40 and 45 degrees 2θ, and one peak between 45 and 50 degrees 2θ in XRD analysis.

[0119] [Table 4]

[0120] [Table 5]

[0121] Furthermore, the coffee grounds composition of Example 0 was found to have diffraction lines with peaks at 2θ=29.3±0.2°, 95.1±0.2°, 99.4±0.2°, and 121.9±0.2° in an XRD analysis.

[0122] Furthermore, the negative electrode material for secondary batteries of Example 1 was subjected to XRD measurement, and the graph of the results is shown in FIG.

[0123] Referring to FIG. 2 and Tables 6 and 7 below, it can be seen that the negative electrode material for secondary batteries shows two peaks between 2θ of 30 and 40 degrees, three peaks between 2θ of 40 and 45 degrees, and two peaks between 2θ of 45 and 50 degrees in XRD analysis.

[0124] [Table 6]

[0125] [Table 7]

[0126] In addition, the degree of orientation of the negative electrode material for secondary batteries is obtained from an XRD pattern obtained by X-ray diffraction measurement, and specifically, it is found that the negative electrode material for secondary batteries has an orientation peak intensity ratio (I110 / I004) of 0.44 in the XRD pattern. That is, when the orientation peak intensity ratio is 0.44, the amount of space that simultaneously enters when lithium ions are inserted into the particles increases, improving the output characteristics, and the direction of expansion during charging is various, and the degree of orientation is low, suppressing expansion in one direction, reducing the electrode expansion rate and improving the life characteristics. Further experimental results of Examples 1-1 to 1-8 show that the orientation peak intensity ratios (I110 / I004) of Examples 1-1 to 1-8 are as follows (see Table 8).

[0127] [Table 8]

[0128] On the other hand, the negative electrode material for secondary batteries containing the coffee grounds composition of the present invention has a DD (Degree of Divergence) value defined by the following formula 1 of 5.96 or more,

[0129] [Formula 1] DD(Degree of Divergence)=(Ia / Itotal)*100

[0130] In the above formula 1, Ia is the total value of peak intensities appearing at 2θ=42.4±0.2°, 43.4±0.2°, 44.6±0.2°, and 77.5±0.2° when measured by XRD using CuKα radiation, and Itotal is the total value of peak intensities appearing at 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2° when measured by XRD using CuKα radiation.

[0131] Table 9 below shows the results of calculating the Ia (total value of peak intensity represented at non-planar angles when XRD is measured using CuKα radiation), Itotal value (total value of peak intensity represented at all angles when XRD is measured using CuKα radiation), and DD (Degree of Divergence) value from XRD data for Example 1 and further experimental Examples 1-1 to 1-8.

[0132] [Table 9]

[0133] It was confirmed that the DD (Degree of Divergence) values ​​were 5.96 to 8.86 in Examples 1-1 to 1-8.

[0134] <Experimental Example 3> Raman spectroscopic analysis results FIG. 3 is a graph showing the results of Raman spectroscopy of a coffee grounds composition according to one embodiment of the present invention, and FIG. 4 is a graph showing the results of Raman spectroscopy of a negative electrode material for a secondary battery including a coffee grounds composition according to one embodiment of the present invention.

[0135] First, the coffee grounds composition of Example 0 was subjected to Raman spectroscopy measurement, and the results are shown in a graph in FIG.

[0136] Moreover, Raman spectroscopy was performed on the negative electrode material for secondary batteries of Example 1, and the results are shown in a graph in FIG.

[0137] Referring to FIG. 4 and Table 10 below, the negative electrode material for secondary batteries has a Raman spectroscopic measurement result of 1350 cm -1 and 1580 cm -1It can be seen that the effective peaks based on ID (D band) and IG (G band) are shown near the respective peaks, and the intensity ratio of the D band and the G band (ID / IG) is 0.41 to 0.98. The D band is a peak indicating the sp3 bond of the silicon oxycarbide, which indicates a carbon crystal having a structural defect, and the G band is a peak indicating the sp2 bond of the silicon oxycarbide, which indicates a carbon crystal without a structural defect.

[0138] [Table 10]

[0139] Here, the D band is a peak indicating the sp3 bond of the silicon oxycarbide and indicates a carbon crystal having structural defects, and the G band is a peak indicating the sp2 bond of the silicon oxycarbide and indicates a carbon crystal without structural defects.

[0140] In the present invention, the term "vicinity" refers to an adjacent area that can be seen at the wave number described in the present specification. For example, in the present invention, cm -1 The effective peak is around 1350 cm -1 In the technical field to which the present invention pertains, the effective peak is usually expressed as 1350 cm -1 In other words, although the wavenumber at which a peak is observed may vary depending on various analytical conditions such as the analyst, analytical equipment, or analytical sample, it means a wavenumber range that is observed at the relevant wavenumber and is generally applicable.

[0141] <Experimental Example 4> XPS analysis results FIG. 5 is a graph showing the results of X-ray photoelectron spectroscopy (XPS) measurement of a coffee grounds composition according to an embodiment of the present invention, and FIG. 6 is a graph showing the results of X-ray photoelectron spectroscopy measurement of a negative electrode material for a secondary battery including a coffee grounds composition according to an embodiment of the present invention.

[0142] First, the coffee grounds composition of Example 0 was subjected to X-ray photoelectron spectroscopy measurement, and the results are shown in a graph in FIG. 5, and the measured values ​​are shown in Table 11 below.

[0143] [Table 11]

[0144] Referring to FIG. 5 and Table 11, the XPS measurement result for the coffee grounds composition shows that the full width at half maximum (FWHM) of the O1s peak on the measured surface is 2.61, and the nitrogen element content is 0.37 atomic %.

[0145] Here, the half-width of the O1s peak measured by XPS indicates the sigma bond of oxygen, and in this application indicates the amount of water (H2O) that does not react with silicon on the surface of the negative electrode material. Therefore, the larger the half-width, the less silicon on the surface of the negative electrode material reacts with water.

[0146] That is, when the half-width of the XPS O1s peak on the surface of the negative electrode material is 2.0 or more, the reaction between silicon and water on the surface of the negative electrode material is sufficiently suppressed, and thus the decrease in the discharge capacity and capacity efficiency of the secondary battery can be suppressed during the time from the manufacture of the negative electrode material to the formation of the negative electrode.

[0147] It can also be seen that the coffee grounds composition exhibits a first XPS effective peak, a second XPS effective peak, a third XPS effective peak, and a fourth XPS effective peak in the binding energy ranges of 281.18 to 291.08 eV, 397.18 to 402.18 eV, 528.48 to 536.88 eV, and 99.88 to 105.08 eV, respectively.

[0148] In the present invention, a "significant or effective" peak means a peak that is repeatedly detected in analytical data such as Raman or XRD in a pattern that is recognized in the art as being substantially the same, without being significantly influenced by the analytical conditions or the person performing the analysis. It is clear that a person having ordinary knowledge in the technical field to which the present invention pertains can easily determine whether or not a peak is a significant or effective peak.

[0149] On the other hand, the negative electrode material for secondary batteries of Example 1 was subjected to X-ray photoelectron spectroscopy measurement, the results of which are shown in a graph in FIG. 6, and the measured values ​​are shown in Table 12 below.

[0150] [Table 12]

[0151] Referring to FIG. 6 and Table 12, the XPS measurement result of the negative electrode material for secondary batteries shows that the full width at half maximum (FWHM) of the O1s peak on the measured surface is 2.09, and the nitrogen content of the negative electrode material is 0.58 atomic % according to X-ray photoelectron spectroscopy (XPS).

[0152] It is also found that the negative electrode material for secondary batteries exhibits a first XPS effective peak, a second XPS effective peak, a third XPS effective peak, and a fourth XPS effective peak in the binding energy ranges of 281.08 to 292.08 eV, 395.68 to 403.78 eV, 528.48 to 537.58 eV, and 99.08 to 108.48 eV, respectively.

[0153] Table 13 below relates to the XPS experimental data for Examples 1-1 through 1-8, which were further studied.

[0154] [Table 13]

[0155] In Examples 1-1 to 1-8, it was confirmed that the full width at half maximum (FWHM) of the O1S peak on the surface measured by XPS was 1.95 to 3.44.

[0156] In addition, in Examples 1-1 to 1-8, it was confirmed that the nitrogen atom content was 0.25 to 1.07 atomic % by X-ray photoelectron spectroscopy (XPS).

[0157] <Experimental Example 5> Tap density and particle size analysis experiment results 7 and 14 show the tap density and particle size analysis results of the coffee grounds composition according to the embodiment of the present invention, and FIG. 8 and FIG. 15 show the tap density and particle size analysis results of the negative electrode material for secondary batteries containing the coffee grounds composition according to the embodiment of the present invention.

[0158] First, the coffee grounds composition of Example 0 was subjected to tap density and particle size analysis, and the results are shown in Figures 7 and 14.

[0159] 7 and 14, the coffee grounds composition has a tap density of 0.48 g / cm 3 It can be seen that the particle size D50 is 317.14 μm.

[0160] Further, the secondary battery negative electrode material of Example 1 was subjected to tap density and particle size analysis, and the results are shown in FIG. 8 and FIG.

[0161] Referring to FIG. 8 and Table 14, the negative electrode material for secondary batteries has a tap density of 0.93 g / cm 3 It can be seen that the particle size D50 is 19.93 μm.

[0162] Further, the tap density measurement results for Examples 1-1 to 1-8 in further experiments are shown in FIG. 15. Samples 1 to 8 in FIG. 15 correspond to Examples 1-1 to 1-8, respectively. The negative electrode material for secondary batteries containing the coffee grounds composition had a tap density of 0.93 to 1.02 g / cm 3 It was confirmed that.

[0163] Also, particle size (D(v,0.5) μm) experimental data for Examples 1-1 to 1-8 for further experiments is shown in Table 14.

[0164] [Table 14]

[0165] It was confirmed that the particle size D50 for Examples 1-1 to 1-8 was 18.15 to 29.46 μm.

[0166] In this way, the negative electrode material for secondary batteries having the above tap density can minimize deformation when pressed with a certain pressure during electrode production and suppress expansion due to charging and discharging. Therefore, when used as a negative electrode material for lithium secondary batteries, the tap density and orientation are improved, and improved effects such as suppression of electrode expansion can be achieved.

[0167] As described above, the present invention has been described in detail using examples. However, since the above examples are merely preferred examples of the present invention, the present invention should not be understood to be limited to the above examples, and the scope of the present invention should be understood to be the claims set forth below and their equivalent concepts.

Claims

1. A negative electrode material for a secondary battery comprising a carbonized coffee grounds composition having nanosilicon intercalated therein, The carbonized nanosilicon-intercalated coffee grounds composition is produced by drying and heat treating a mixture comprising coffee by-products and coffee grounds, and nanosilicon; The negative electrode material for secondary batteries containing the carbonized coffee grounds composition having nanosilicon intercalated therein is characterized in that, in an XRD analysis, it shows two peaks between 2θ of 30 and 40 degrees, three peaks between 2θ of 40 and 45 degrees, and two peaks between 2θ of 45 and 50 degrees.

2. The negative electrode material for secondary batteries according to claim 1, characterized in that the negative electrode material for secondary batteries containing the carbonized coffee grounds composition having nanosilicon intercalated therein has an orientation peak intensity ratio (I110 / I004) of an XRD pattern of 0.44 to 0.

81.

3. The negative electrode material for a secondary battery including the carbonized coffee grounds composition having nanosilicon intercalated therein has a degree of divergence (DD) value defined by the following Equation 1 of 5.96 to 8.86, [Formula 1] DD (Degree of Divergence) = (Ia / Itotal) * 100 In the formula 1, Ia is a total value of peak intensities appearing at 2θ=42.4±0.2°, 43.4±0.2°, 44.6±0.2°, and 77.5±0.2° in XRD measurement using CuKα radiation, and Itotal is a total value of peak intensities appearing at 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2° in XRD measurement using CuKα radiation. The negative electrode material for secondary batteries according to claim 1,

4. The negative electrode material for secondary batteries containing the carbonized coffee grounds composition into which nanosilicon has been inserted has a Raman spectroscopic measurement result of 1350 cm -1 and 1580 cm -1 2. The negative electrode material for secondary batteries according to claim 1, characterized in that the negative electrode material exhibits effective peaks due to the D band and the G band around the vicinity of the D band and the G band, respectively, and the intensity ratio (ID / IG) of the D band and the G band is 0.41 to 0.

98.

5. The negative electrode material for secondary batteries according to claim 1, characterized in that the negative electrode material for secondary batteries containing the carbonized coffee grounds composition having nanosilicon intercalated therein has a full width at half maximum (FWHM) of an O1s peak on the surface measured by X-ray photoelectron spectroscopy (XPS) of 1.95 to 3.

44.

6. 2. The negative electrode material for secondary batteries according to claim 1, wherein the carbonized coffee grounds composition having nanosilicon intercalated therein has a nitrogen element content of 0.25 to 1.07 atomic % by X-ray photoelectron spectroscopy (XPS).

7. The negative electrode material for secondary batteries comprising the carbonized coffee grounds composition having nanosilicon intercalated therein exhibits a first XPS effective peak, a second XPS effective peak, a third XPS effective peak, and a fourth XPS effective peak in binding energy ranges of 281.08 to 292.08 eV, 395.68 to 403.78 eV, 528.48 to 537.58 eV, and 99.08 to 108.48 eV, respectively. The negative electrode material for secondary batteries according to claim 1,

8. 2. The negative electrode material for secondary batteries according to claim 1, wherein the carbonized coffee grounds composition having nanosilicon intercalated therein has an initial charge capacity of 243.1 to 288.5 mAh / g and an initial discharge capacity of 241.3 to 287.3 mAh / g.

9. The negative electrode material for secondary batteries containing the carbonized coffee grounds composition having nanosilicon intercalated therein has a tap density of 0.93 to 1.02 g / cm 3 2. The negative electrode material for secondary batteries according to claim 1,

10. 2. The negative electrode material for secondary batteries according to claim 1, wherein the nanosilicon-intercalated carbonized coffee grounds composition has a particle size D50 of 18.15 to 29.46 μm.

Citation Information

Patent Citations

  • Preparation method of hard carbon negative electrode material of sodium ion battery

    CN111204731A

  • JP10-0903503B

  • JP10-1334594B

  • JP10-1613518B

  • Negative electrode material for lithium secondary battery, its manufacturing method, and lithium secondary battery

    JP2006196234A